HUBUNGAN BERBAHASA, BERPIKIR, DAN BERBUDAYA - Nandang Sarip Hidayat (Sosial Budaya, 2014)
The Net is the process of delivering information in communication. According to Abdul Chaer: Speaking is delivering thoughts or feelings of the people who spoke about the problems faced in its cultural life. Language is what we would call mind and there's no other way to think about reality except through language. Thus the activities of cultural events are also speaking. Speak not just stylish but express themselves in life. There are several theories about the relationship of language, thought and culture. Von Humbolt Di antarannya Wihelm theory is the view of a society is determined by the language, the Sapir-Whorf theory that language as a tool of thought, theory of Piaget, Bruner theory, theory Lenneberg, Chomsky and Vygosky. So speaking activities, thinking and culture are three inter-related activities in human activity